Toward accurate ab initio modeling of siliceous zeolite structures - Trachta, Michal; Rubeš, Miroslav; Bludský, Ota (The Journal of chemical physics, 2022)
Structures of purely siliceous materials in the International Zeolite Association database were investigated with four different theoretical methods ranging from the empirical approaches, such as the distance least squares and force fields to the computationally demanding dispersion-corrected density functional theory method employing the generalized gradient approximation-type functional. The structural characteristics were first evaluated for dense silica polymorphs, for which reliable low-temperature experiments are available. Due to the significant errors in experimentally determined atomic positions of siliceous zeolites, lattice parameters and the cell volume were proposed as reliable descriptors for the structural assessment of zeolite frameworks. In this regard, the most consistently performing (systematically underestimating/overestimating) methods are the Sanders-Leslie-Catlow (SLC) force field and the PBEsol density functional. The best overall agreement with the experiment is observed for PBEsol-D2. However, it is a result of fortuitous error cancellations rather than improved description upon adding dispersion correction. We proposed two approaches to estimate accurate cell volumes of siliceous materials from theoretical data: (i) using the SLC and PBEsol volumes as lower and upper bounds and (ii) using a structural response to the dispersion correction along with the SLC compressibility as an additional criterion.